Does sperm DNA fragmentation correlate with semen parameters? - Le, Minh Tam (Reprod Med Biol, 2019)
PURPOSE: This study aimed to investigate the association between sperm quality assessed by routine semen analysis and sperm DNA integrity assay. METHODS: In our cross‐sectional study, a total of 318 men from the infertile couples were enrolled from December 2017 to March 2019 at the Hue Center for Reproductive Endocrinology and Infertility, Vietnam. General characteristics and semen parameters were detected. The sperm DNA fragmentation index (DFI) was estimated by the sperm chromatin dispersion (SCD) assay. A threshold of DFI 30% was applied to classify normal (DFI < 30%) or abnormal (DFI ≥ 30%) groups. The correlations between DFI and semen parameters were analyzed by Spearman's rank correlation coefficient. RESULTS: In the correlation analysis, DFI was significantly correlated with abnormal head and progressive motility, with a positive correlation with abnormal head (ρ = .202, P = .0003) and a weak negative correlation with progressive motility (ρ = −.168, P = .0027), respectively. In the bivariate analysis, DFI was associated with male age, smoking, and alcohol consumption with P < .05. CONCLUSIONS: The sperm DFI was not strongly correlated with conventional semen parameters. Therefore, a sperm DNA fragmentation assay should be performed as an additional step in the investigation of male fertility.